Long-Term Follow-Up with Ross Procedure at a Single Institution in China - Xu, Zhiwei; Li, Wenbin; Xu, Xiufang; Zhou, Zifan; Song, Shiqiu; Ma, Jinghui; Zhang, Jianqun (The Thoracic and Cardiovascular Surgeon, 2014)
Background Although the Ross operation requires double-valve replacement for aortic valve disease, it has been shown to provide excellent hemodynamic results and is associated with low morbidity and mortality rates. We reviewed our long-term experience after completion of the Ross procedure.Methods Between October 1994 and February 2009, 58 consecutive patients underwent a Ross procedure at our institution. The right ventricular outñow tract was repaired with a cryopreserved pulmonary homograft. All patients were scheduled for a yearly study thereafter that ended at the time of death or at closure of the follow-up visit. Mean follow-up was 8.2 ± 3.5 years (range: 1.8 to 16.2 years).Results There were two early deaths (3%) and one late death (2%). Actuarial survival at 16 years was 94.8 ± 3.1%. One patient required reoperation and died during reoperation 1.5 years after his first Ross operation. Of the 55 survival patients, 42 patients (76%) were in NYHA functional class I and 13 patients (24%) were in NYHA functional class II. Grade 1 or grade 2 autograft regurgitation was observed in seven patients (12%) at 1 year after the surgery. The sinus of Valsalva diameters were all <40 mm in these seven patients. Freedom from hemodynamically relevant autograft regurgitation was 88 ± 2.8% at 16 years. After surgery, left ventricular function was significantly improved and left ventricular end-diastolic diameter recovered to normal over the long term. None of the patients required reoperation due to pulmonary homograft failure.Conclusions The Ross procedure can be safely performed in patients with aortic valve disease. To date, mortality, morbidity, and reoperation rates are very low. Reasons for these superior results may include the following: (1) the diameter of the aortic valve annulus matching that of the pulmonary valve and (2) patients were monitored with antihypertensive medications to keep systolic blood pressure under 120 mm Hg to delay pressure lesions to the pulmonary autograft.
Keywords: aortic valve and root; heart valve Surgery; pulmonary valve